2012
DOI: 10.1007/s00436-012-2883-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of bovine giardiasis and endemic genetic characterization of Giardia duodenalis isolates in Heilongjiang Province, in the Northeast of China

Abstract: To determine the prevalence of bovine giardiasis in Heilongjiang Province in China and to molecularly characterize Giardia duodenalis, feces were collected from 814 dairy and beef cattle ranging in age from 6 days to 9 years. Clinical symptoms of diarrhea were recorded at the time of sampling. The G. duodenalis infection rate in cattle was 5.2 % (42/814) as determined by Lugol's iodine staining. G. duodenalis assemblages and subtypes were genetically diagnosed by sequence analysis of the triosephosphate isomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
28
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
12
28
3
Order By: Relevance
“…Previous reports showed that assemblage A is more prevalent in pre-weaned calves than the older cattle (Mark-Carew et al, 2012;Trout et al, 2007;Wang et al, 2014). In our study, however, the vast majority of G. duodenalis isolates detected in calves were characterized as assemblage E. This finding was in accordance with previous reports regarding giardiasis as a common infection in younger farm animals (Liu et al, 2012;Wade et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports showed that assemblage A is more prevalent in pre-weaned calves than the older cattle (Mark-Carew et al, 2012;Trout et al, 2007;Wang et al, 2014). In our study, however, the vast majority of G. duodenalis isolates detected in calves were characterized as assemblage E. This finding was in accordance with previous reports regarding giardiasis as a common infection in younger farm animals (Liu et al, 2012;Wade et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the overall infection rate of G. duodenalis in cattle, ranging from newborn to 2 years old, was 7.2% (128/1777), which is a little higher than that recently reported in same-aged cattle in Heilongjiang Province, China (6.4%, 41/643) [24]. As is well known, the determinants of infection rates are complex and the rates are often affected by many factors, including the ages of the animals, sample size, examination methods, different management systems, the timing of specimen collection, and geoecological conditions.…”
Section: Discussioncontrasting
confidence: 63%
“…However, there has been only one study of G. duodenalis infection in calves in Heilongjiang, China [24]. Therefore, because there are relatively few prevalence data available on G. duodenalis in cattle in China and an even greater lack of molecular data, we determined the prevalence of G. duodenalis in dairy cattle in Henan, China, and characterized it at the molecular level, using multilocus genotyping at the SSU rRNA, β-giardin ( bg ), glutamate dehydrogenase ( gdh ), and triosephosphate isomerase ( tpi ) loci.…”
Section: Introductionmentioning
confidence: 99%
“…In this assemblage of our study, nucleotide sequences of the SSU rRNA gene was identical to human isolates in the Netherlands (AY826207, van der Giessen et al, 2006) and USA (U09492, van Keulen et al, 1995), a monkey isolate in Spain (HQ616612, Martínez-Díaz et al, 2011), and a horse isolate in Colombia (JX972180, Santín et al, 2013). No SNP was found at tpi and gdh loci, which were identical to reference sequences in dairy cattle in China (JN162356, Liu et al, 2012) and horses in Colombia (JX972185, Santín et al, 2013), respectively. There was only one subtype at the bg locus, which demonstrated 100% identity with human isolates in India (JF918481, unpublished paper), Egypt (HM171690, unpublished paper) and Australia (HQ179587, Wielinga et al, 2011).…”
Section: G Intestinalis Assemblages and Subtypesmentioning
confidence: 70%